Enhancing the Antibiotic Antibacterial Effect by Sub Lethal Tellurite Concentrations: Tellurite and Cefotaxime Act Synergistically in Escherichia Coli - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Muñoz-Villagran, C; Molina-Quiroz, R (2012)
The emergence of antibiotic-resistant pathogenic bacteria during the last decades has become a public health concern worldwide. Aiming to explore new alternatives to treat antibiotic-resistant bacteria and given that the tellurium oxyanion tellurite is highly toxic for most microorganisms, we evaluated the ability of sub lethal tellurite concentrations to strengthen the effect of several antibiotics. Tellurite, at nM or ?M concentrations, increased importantly the toxicity of defined antibacterials. This was observed with both Gram negative and Gram positive bacteria, irrespective of the antibiotic or tellurite tolerance of the particular microorganism. The tellurite-mediated antibiotic-potentiating effect occurs in laboratory and clinical, uropathogenic Escherichia coli, especially with antibiotics disturbing the cell wall (ampicillin, cefotaxime) or protein synthesis (tetracycline, chloramphenicol, gentamicin). In particular, the effect of tellurite on the activity of the clinically-relevant, third-generation cephalosporin (cefotaxime), was evaluated. Cell viability assays showed that tellurite and cefotaxime act synergistically against E. coli. In conclusion, using tellurite like an adjuvant could be of great help to cope with several multi-resistant pathogens. © 2012 Molina-Quiroz et al.